Facebook addiction and social skills in students of a private university in Lima - Mejía Bejarano, Gabriela (2019)
Objective: determine whether there is significant relationship between dependence on facebook social skillsin students of a private university in Lima, Peru. Material and Methods: This was applied to a sample of 300students test Young Internet Addiction adapted and validated by Mariani (2005), to measure the level of addictionto the social networking and social skills scale ( Gismero , 2000 ), with to assess skill levels in this area. Theresearch was conducted from a non- experimental methodology, cross-sectional and descriptive correlational.Results: Among the significant findings of the study, it was found that 10.3 % had a level of addiction to facebook,regarding social skills, 56.3 % reported a low level. Moreover it was found that there was a highly significantinverse correlation (p evalue = 0.001). Conclusions: This confirms that the dependence facebook inverselyrelated to social skills of young people.